Interreligious Tolerance in the Perception of Maluku Muslim Society - Amri, Muhammad; Mosiba, Risna; Bin-Tahir, Saidna Zulfiqar (Jurnal Adabiyah, 2020)
All religions teach peace and welfare to their adherents through tolerance. The religious teaching, however, can also be the trigger of interreligious conflicts as it happened in Ambon in 1999-2011. This study aims at determining whether or not the knowledge, education level, perception, and attitudes of the Ambones’ Muslim community affect the interreligious tolerance in Ambon. This research employed quantitative research using survey design. The sample of the study consisted of 100 Muslims in Ambon city. The data have been collected through a questionnaire distributed, and they have been analyzed descriptively and inferentially using the SPSS program. The results found that the knowledge, level of education, perception, and attitude of the Ambones’ Muslim community collectively had a positive impact on the interreligious tolerance amongst the Ambones’ community. However, this perception has no significant effect on tolerance partially. The results of this study contributed to prevent and manage further unpredictable of interreligious conflict in the city of Ambon, Maluku. الملخصتعلم جميع الأديان السلام والازدهار للمعتندين من خلال التسامح. ومع ذلك ، يمكن أن تكون التعاليم الدينية أيضًا محفزًا للصراع بين الأديان كما حدث في أمبون في 1999-2011. تهدف هذه الدراسة إلى تحديد ما إذا كانت المعرفة ، ومستوى التعليم ، وتصورات ومواقف المجتمع المسلم في أمبون تؤثر على التسامح بين الأديان في مالوكو. يستخدم هذا البحث البحث الكمي باستخدام تصميم المسح. تكونت عينة البحث من 100 مسلم في مدينة أمبون. تم جمع البيانات من خلال استبيان وتحليلها وصفيًا واستنتاجيًا باستخدام SPSS 19. ووجدت نتائج الدراسة أن معرفة ومستوى التعليم والإدراك وموقف المجتمع الإسلامي في أمبون بشكل جماعي كان لها تأثير إيجابي على التسامح بين الأديان بين شعب أمبون. ومع ذلك ، ليس لهذا التصور تأثير كبير على التسامح الجزئي. تساهم نتائج هذه الدراسة في منع وإدارة الصراع بين الأديان الذي لا يمكن توقعه أكثر في مدينة أمبون ، مالوكو.الكلمات المفتاحية: التصور ، مسلمو مالوكو ، الموقف ، التسامح بين الأديان                                                                         AbstrakSemua agama mengajarkan perdamaian dan kesejahteraan bagi penganutnya melalui toleransi. Namun, ajaran agama juga bisa menjadi pemicu konflik antaragama seperti yang terjadi di Ambon pada 1999-2011. Studi ini bertujuan untuk menentukan apakah pengetahuan, tingkat pendidikan, persepsi, dan sikap komunitas Muslim Ambon mempengaruhi toleransi antaragama di Maluku. Penelitian ini menggunakan penelitian kuantitatif dengan menggunakan desain survei. Sampel penelitian terdiri dari 100 Muslim di kota Ambon. Data dikumpulkan melalui kuesioner dan dianalisis secara deskriptif dan inferensial menggunakan program SPSS 19. Hasil penelitian menemukan bahwa pengetahuan, tingkat pendidikan, persepsi, dan sikap komunitas Muslim Ambon secara kolektif memiliki dampak positif pada toleransi antaragama di antara masyarakat Ambon. Namun, persepsi ini tidak berpengaruh signifikan terhadap toleransi secara parsial. Hasil dari penelitian ini berkontribusi untuk mencegah dan mengelola konflik antaragama yang tidak dapat diprediksi lebih lanjut di kota Ambon, Maluku.